Alfabetización Mediática e Informacional (AMI) en tiempos de Desinformación: perspectivas en Iberoamérica. - RODRÍGUEZ CRUZ, Yunier; MEDINA-GONZÁLEZ, Viena; ALMANSA-MARTÍNEZ, Ana (Chasqui (13901079))
Media and Information Literacy (MIL) has contributed to the understanding and adaptation to the major evolutionary and cultural changes of the digital transformation. This research aims to focus on the challenges of ensuring digital citizenship with critical thinking and skills that can reduce the negative effects of disinformation. The study uses documentary analysis to examine theoretical elements on the topic and consults Ibero-American researchers and experts who have worked on it. Among the main results, elements associated with misinformation that should be strengthened in MIL programs are focused. These components would contribute to fostering skills and a digital culture that allows for critically addressing the disinformation processes that are generated today in the media and public sector.